Вы находитесь на странице: 1из 9

8

8.
.
.
(1) .
, ,
[b]. ,
:

d [ B ]L
SL = k1[ A]L SL k1[ B]L SL [ B]L B S = 0
dt
d [ B ]L
1
= k1[ A]L k1[ B]L [ B]L = 0

dt
[ B ]L [ B ]L + [b]
d [ B ] + [b]
1
= ( k1[ A]L k1 ([ B]L + [b]) ) ([ B]L + [b])

dt
d [b]
1
1
= k1[b] [b] = ( k1 + )[b]

dt
[b] ( t ) = [b] ( t = 0 ) e

1
( k 1 + ) t

[b] ( t ) 0, t

(1)

,
. . , ,
.
.
1.
.
2.

.
3.
.
-.
k1
A + X
2X
k2
X + Y
2Y

(2)

k3
Y + B
2E

8
, ( ).
,
. X Y
.

d[ X ]
= k1[ A][ X ] k2 [Y ][ X ] = 0
dt

(3a)

d [Y ]
= k2 [Y ][ X ] k3[Y ][ B] = 0
dt

(3)

(4)

Y , (4) X

[Y ] =

k1[ A]
k2

(4a)

[ ] =

k3 [ ]
k2

(4)

[X](t) = [X] + [x]0 (t); [Y] (t) = [Y] + [y]0 (t)

[x]0(t)/[X] (t) <<1;

[y]0 (t)/[Y] (t) <<1

(5)

[x]0(t) [y]0(t). :

d {[ X ] + [ x]0 }
= k1[ A][ X ] + k1[ A][ x]0
dt
k2 [Y ] [ X ] k2 [ y ]0 [ X ] k2 [Y ] [ x]0

d {[Y ] + [ y ]0 }
= k2 [Y ] [ X ] + k2 [ y ]0 [ X ] + k2 [Y ] [ x]0
dt
k3[ B ][Y ] k3[ B ][ y ]0
(6)
(6) , [y]0, [x]0

, (5).

. (4) (6),
:

d [ x]0
= k1[ A][ x]0 k2 [ y ]0 [ X ] k2 [Y ] [ x]0 =
dt
k [ B]
k [ A]
k1[ A][ x]0 k2 [ y ]0 3
k2 1 [ x]0 = k3[ y ]0 [ B ]
k2
k2

(7)

d [ y ]0
= k2 [ y ]0 [ X ] + k2 [Y ] [ x]0 k3[ B ][ y ]0 =
dt
k [ B]
k [ A]
k2 [ y ]0 3
+ k2 1 [ x]0 k3[ B ][ y ]0 = k1[ x]0 [ A]
k2
k2

(8)

(8) :

d 2 [ y ]0
d [ x]0
=
k
[ A]
1
2
dt
dt

(9)

d [ x]0
(8)
dt

d 2 [ y ]0
= k1k3[ B][ A][ y ]0 (t ) = [ y ]0 (t )
dt 2

d 2 [ y ]0
+ [ y ]0 (t ) = 0
2
dt

(10)

= k1k3[ A][ B] > 0


P (10)

[y]0 (t) = 2 sin (1/2 t) + 1 cos (1/2 t)

(11)

[y]0 (t) (11) (8) []0 (t)

[x]0 (t) = (2 1/2/k1[A])*cos (1/2 t) - (1 1/2/k1[A]) sin (1/2 t)

(12)

t = 0,

[y]0 (t=0) = [y0]0 ,

[x]0 (t=0) = [x0]0

1 = [y0]0 ( (11));
2 = [x0]0*k1[A]/ (1/2) = [x0]0*(k1[A]/ k3[B])1/2 ( (12))
:

[y]0 (t) = [x0]0*(k1[A]/ k3[B])1/2 sin (1/2 t) + [y0]0 cos (1/2 t)


[x]0 (t) =
([x0]0*k1[A]* 1/2/(1/2)* k1[A])*cos (1/2 t) - ([y0]0 1/2/k1[A]) sin (1/2 t) =
([x0]0*cos (1/2 t) {[y0]0 (k3[B] /k1[A])1/2} sin (1/2 t)

(13)

Y2

1.5

[Y]0(t), [X]0(t)

1.0

0.5

Y1

0.0

x1

-0.5

[X]0(t)

x1

-1.0

[Y]0(t)
-1.5
0

200

400

600

800

[y]0(t)


[y]0 (t) - [x]0 (t), .
1.5

Y2

1.0

0.5

Y1
0.0

-0.5

-1.0

-1.5

X1
-0.2

-0.1

0.0

0.1

0.2

[x]0(t)

.
.
.
k1
X + A
2X
k2
X
B

(14)

k3
3 X
B + 2X

d[ X ]
= k1[ A][ X ] k2 [ X ] k3[ X ]3 = 0
dt

(15)

d[ X ]
= R[ X ] k3[ X ]3 = 0
dt

(16)

R = k1[ A] k2
R , [A] . , [A]
, . .
R

<0, :
R <0,

[X]. = 0

(
, ).
R>0 :

R >0,

[X]. = 0,

[X]. =

R
k3

R =

0 - , , - .
, R <0 [X]. = 0 , R >0, - .

[X](t). = [X]. + [x](t)


, , -:

d [ X ] + d [ x](t )
2
= R[ X ] + R[ x](t ) k3[ X ]3 3k3[ x](t )[ X ]
dt
(17)

(16) (17) [X].= 0.

d [ x](t )
= R[ x](t )
dt

(18)

[ x](t ) = [ x](t = 0) e Rt

(19)

R>0,
, . ,
R<0, ,

[X].= 0.

R=0, :
1) , ,
.
2) .
R=0 .
, R>0, .
.

. L D - .
. . ,
- L . D .
.
. , L D .
, .
,
.
( ):
k1

X L;
S + T

k1

k1

XD
S + T

k2

2X L
S + T + X L
k2

2 X D
S + T + X D

k1

(20)

k2

k2

k3
X L + X D
P

8
(20) . S -
. .
L D :

d[XL]/dt =
=k1[S][T] - k-1[XL] + 2 k2 [S][T] [XL] k-2[XL]2 - k3[XL] [XD]

(21)

d[XD]/dt =
= k1[S][T] - k-1[XD] + 2 k2 [S][T] [XD] k-2[XD]2 - k3[XL] [XD]

(22)

(21) (22) , (22)

(21) (21) (22). , , (23)


, (24) :
d
= k1 + k2 2k2
dt
d
= k1 k1 + k2 k2 ( 2 + 2 ) k3 ( 2 2 )
dt

(23,24)

(23) (24) :

= [ S ][T ]
[XL][XD]
2
[X ] +[XD]
= L
2

(23) L

D. , (23) =0.
. .
, , , :

d
=0
dt
k1 + k2 2k2 = 0

(25)

0
(25)

(24)
. , ,

, ,
!
, , - .

,

!
, ,
,
.